Palliative care for the elderly in long stay institutions: a gesture of love : Palliative care for elderly people in long-stay institutions: an integrative review (Health and Biosciences, 2023)
In recent years, the number of elderly people requiring palliative care in Long-Term Care Institutions has increased considerably. Thus, it is observed the need to provide specific and targeted care to these elderly, in order to provide a higher quality of life to them. This study aims to identify the aspects involving palliative care provided to the elderly in specialized institutionalized homes for the elderly. This is an integrative literature review, using Lilacs (Latin American and Caribbean Literature in Health Sciences), Scielo (Scientific Electronic Library Online) and MedLine/Pubmed (Online system for searching and analyzing medical literature), through VHL (Virtual Health Library), for this research and selection of studies. From 13 studies researched, 7 articles published in the last 11 years that met the criteria of this review were selected. In the research carried out, factors related to palliative care in the elderly were identified such as: the context that encompasses palliative care, the difficulties in providing care by professionals and the essentiality of humanization in palliative care. Conclusion: With this review, it was possible to observe that the only care model still persists, in addition, it was noticed the need for policies that regularize the profession of caregivers and standardize their hiring, in addition to the insertion of educational measures that improve the work of the multidisciplinary team in long-term institutions.
Keywords: Keywords: Palliative care; Comprehensive care for the elderly; Multi-professional team.